2020
DOI: 10.5897/ajb2020.17101
|View full text |Cite
|
Sign up to set email alerts
|

Bio-appraisal of three strains of lactobacillus based probiotics on the growth traits and semen characteristics of local toms

Abstract: The effect of three strains of Lactobacillus based probiotics on the growth performance and semen quality of toms was conducted in a thirty-four week study. Eighty day-old (d 1) poults were randomly divided into 4 groups, replicated twice with 10 birds per replicate and assigned to four treatments; T1 (Lactobacillus delbrueckii subsp Bulgaricus), T2 (Lactobacillus acidophilus), T3 (Lactobacillus sporogens) and T4 (control), in a completely randomized design (CRD). Feed and water were supplied ad libitum. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A study conducted by Dim et al [ 60 ] using Lactobacillus acidophilus NRRL-4495 (10 8 CFU/ml) in chicks demonstrated improvement in semen quality, sperm concentration (5.82 × 10 9 /ml), progressive motility (82.93%), live sperm (94.13%), dead sperm (5.87%), normal sperm (91.38%), and abnormal sperm (8.62%). Probiotics' role in producing trace minerals and vitamins in the birds' intestines, which boosts the quality of the sperm, may be responsible for the enhanced sperm quality.…”
Section: Implication Of Lactic Acid Bacteria On Animal Fertility-rela...mentioning
confidence: 99%
“…A study conducted by Dim et al [ 60 ] using Lactobacillus acidophilus NRRL-4495 (10 8 CFU/ml) in chicks demonstrated improvement in semen quality, sperm concentration (5.82 × 10 9 /ml), progressive motility (82.93%), live sperm (94.13%), dead sperm (5.87%), normal sperm (91.38%), and abnormal sperm (8.62%). Probiotics' role in producing trace minerals and vitamins in the birds' intestines, which boosts the quality of the sperm, may be responsible for the enhanced sperm quality.…”
Section: Implication Of Lactic Acid Bacteria On Animal Fertility-rela...mentioning
confidence: 99%